A Flexible Human-Agent Interaction model for supervised autonomous systems - Mostafa S.A.; Ahmad M.S.; Ahmad A.; Annamalai M.; Gunasekaran S.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Autonomous agents; Robotics; Software agents; Adjustable autonomy; Autonomous capability; Autonomous systems; Flexible mechanisms; Human agent interactions; Multi-agent technologies; Unmanned aerial systems; Multi agent systems